2015
DOI: 10.1016/j.ifset.2015.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Irradiation as a novel approach to improve quality of Tropaeolum majus L. flowers: Benefits in phenolic profiles and antioxidant activity

Abstract: Edible flowers are increasingly used in food preparations, requiring new approaches to improve their conservation and safety. Food irradiation, particularly electron beam and gamma irradiation, is legally recognized to extend shelf life, improve hygienic quality and disinfest foods. Garden nasturtium (Tropaeolum majus L.) flowers are widely used in food preparations, being also known for their antioxidant properties and high content of phenolics. The purpose of this study was to evaluate the dose-response effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 24 publications
1
15
0
3
Order By: Relevance
“…The irradiation was able to increase the antioxidant activity, especially when applying the dose of 0.5 kGy, which is in agreement with the highest concentration of phenolic compounds found in this sample (Table 3). Koike and co-authors reported an increase in the antioxidant activity of V. tricolor (Koike et al, 2015a) and T. majus (Koike et al, 2015b) subjected to irradiation treatment, especially at the dose of 1 kGy, which also gave the highest amount in phenolic compounds. Concerning the cytotoxic activity (Table 4), B. variegata L. var.…”
Section: Effects Of Electron Beam Irradiation On the Bioactive Propermentioning
confidence: 96%
See 4 more Smart Citations
“…The irradiation was able to increase the antioxidant activity, especially when applying the dose of 0.5 kGy, which is in agreement with the highest concentration of phenolic compounds found in this sample (Table 3). Koike and co-authors reported an increase in the antioxidant activity of V. tricolor (Koike et al, 2015a) and T. majus (Koike et al, 2015b) subjected to irradiation treatment, especially at the dose of 1 kGy, which also gave the highest amount in phenolic compounds. Concerning the cytotoxic activity (Table 4), B. variegata L. var.…”
Section: Effects Of Electron Beam Irradiation On the Bioactive Propermentioning
confidence: 96%
“…Moreover, extractability increase could also be explained by the capacity of irradiation to break chemical bonds that link polyphenols to other molecules, thereby releasing soluble phenols of low molecular weight and leading to an increase of antioxidant-rich phenolics (Alothman, Bhat, & Karim, 2009). Koike and co-authors evaluate the dose-response effects of gamma and electron beam irradiation (0.5, 0.8 and 1 kGy) of Viola tricolor L. (Koike et al, 2015a) and Tropaeolum majus L. (Koike et al, 2015b), verifying that electron beam was the most efficient technique to be applied at the dose of 1 kGy. However, this dose was not the most efficient in the flower samples studied in this work, which showed to be more susceptible to degradation when higher doses are applied.…”
Section: Nm) Peak 3 ([M−h]mentioning
confidence: 97%
See 3 more Smart Citations